Establishing exclusive breastfeeding among in-patient malnourished infants in a rural Kenyan hospital: mothers' experiences of a peer supporter intervention - Jane Kahindi; Caroline Jones; James A. Berkley; Martha Mwangome (BMC, 2020)
Abstract Background The 2013 WHO guidelines for nutritional rehabilitation of hospitalized and non-hospitalized malnourished infants under six months (u6m) recommend the re-establishment of exclusive breastfeeding. However, in most low-income settings these recommendations are not consistently applied. A recently concluded pilot study on the effects of implementing these guidelines among hospitalized malnourished infants u6m of age in Kilifi, Kenya introduced breastfeeding peer supporters (BFPS) to the inpatient setting to support guideline implementation. Here we report a sub-study investigating mothers' experiences and perceptions of the process of re-establishing exclusive breastfeeding during their infant's admission to hospital. Methods Interviews were conducted with mothers just prior to their infant's discharge to explore their experiences and perceptions of the breastfeeding support process. A trained social science researcher conducted the interviews in Kiswahili language using a structured interview guide with open questions. Interviews were tape recorded, transcribed and translated into English for analysis. Data were managed and organized using NVIVO version 10 and analyzed using a framework approach. Results Twenty mothers were interviewed. While some mothers found re-establishing breastfeeding challenging, they all reported improved knowledge on the relationships between maternal nutrition, stress management, hygiene practices and breastmilk production. They also reported gaining skills in breast care, breastfeeding techniques, hand expression and handling of expressed breastmilk. The breastfeeding peer supporters were said to have provided technical, social and emotional support which facilitated the process of re-establishing exclusive breastfeeding. The mothers identified the key characteristics of an effective and trustworthy BFPS as well as gaps in support. Conclusion BFPS are able share knowledge and skills in a way that is understood and appreciated by the mothers of inpatient malnourished infants u6m of age, enhancing the reestablishment of exclusive breastfeeding. Central to the success of BFPS is their ability to develop close and supportive relationships with the mothers based on shared social and cultural backgrounds. Future studies should focus on evaluating the long-term impact of inpatient breastfeeding support strategies on the quality of breastfeeding and growth, as well as on understanding where, when and how BFPS might be incorporated into routine hospital settings.